2012
DOI: 10.1002/clc.21954
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Related Physical Activity Among Cardiovascular Specialists

Abstract: Background: Strong evidence supports positive correlation of physical activity with health benefits. Current recommendations by the American Heart Association are a minimum 30 minutes of moderate physical activity 5 days per week. This goal has been equilibrated with 10,000 steps per day. Hypothesis: Work-related physical activity of cardiovascular (CV) specialists does not meet the currently recommended daily physical activity. Methods: Eight cardiothoracic (CT) surgeons, 7 general cardiologists, 5 procedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
13
0
3
Order By: Relevance
“…The results of this study are in line with Abd et al (2012), who showed that cardiologists and cardiac surgeons achieved a similar level of physical activity of 5000 to 6000 steps per day (Abd et al 2012). According to the pedometer index of Tudor-Locke and Bassett (2004), the work-related physical activity of physiotherapists in Germany should be classified as 'low active' (Tudor-Locke and Bassett 2004).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study are in line with Abd et al (2012), who showed that cardiologists and cardiac surgeons achieved a similar level of physical activity of 5000 to 6000 steps per day (Abd et al 2012). According to the pedometer index of Tudor-Locke and Bassett (2004), the work-related physical activity of physiotherapists in Germany should be classified as 'low active' (Tudor-Locke and Bassett 2004).…”
Section: Discussionsupporting
confidence: 82%
“…The creation of activity-promoting infrastructure at work can also be beneficial for medical personnel; for example, it was shown that cardiologists only walked between 5000 and 6000 steps per working day (Abd et al 2012), instead of the recommended amount of 10,000 to 12,000 steps per day (Rütten and Pfeifer 2016). In the German healthcare system, there are approximately 197,000 physiotherapists (Statistisches Bundesamt 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the work performed by outpatient rehabilitation therapist may limit the requirements for therapists to walk during their workday. When compared to other healthcare professionals working in the inpatient environment, our study reported lower step counts for PTs as compared to the physicians working in an urban medical center [ 23 ]. They assessed the average daily step counts for general cardiologists, CT surgeons, procedural cardiologists, and cardiac anesthesiologists using a pedometer and found daily step counts of 6540, 6039, 5910 and 5553, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Weitere Studien belegen ein mittleres Schrittpensum von durchschnittlich 4.000 bis 6.500 Schritte pro Tag in der Bevölkerung bzw. ein Schrittdefizit von 3.500 bis 6.000 Schritte pro Tag in Bezug auf das empfohlene Schrittpensum von täglich 10.000 Schritten [1,35].…”
unclassified
“…das Gehpensum in Schritten pro Tag objektiv zu erfassen [1,36] sowie eine motivationale Unterstützung zur Förderung von körperlicher Aktivität zu geben [30]. Die wissenschaftliche Literatur belegt positive gesundheitliche Effekte sowie eine nachweisbare Steigerung der körperlichen Aktivität durch inner-bzw.…”
unclassified